New Voices in the Old South: Latino Immigrant Students' Experiences at one Georgia Middle School - Bush, Lucy Joanna (2007)
This research study investigated the experiences of Latino immigrant students as they negotiated and developed their academic identities at one Georgia middle school in Athens, Georgia, U.S.A. Seventy-five students took part in the survey portion of the research study, while six students participated in in-depth interviews that formed the ethnographic case studies of this research. I utilized an ethnographic case study approach (Stake, 1995; 1998) in order to explore how these students' academic experiences influenced the negotiation and development of their academic identities into three distinct forms: cholo or low-performing, medio or average-performing, and cabezon or highperforming. Each of the case study participants is of Mexican heritage. The students had varied experiences at the research site, leading to the development of differing academic identities. Perceptions of teacher support, self-efficacy, parental involvement, school environment, and availability of extracurricular activities influenced the negotiation and development of said academic identities. There is substantial previous research regarding the academic experiences of immigrant students, but almost none focuses on the experiences of immigrant middle school students in their own words. Through the power of their voice, these students heartbreakingly describe discrimination, hatred, and intolerance. They also speak to the innocence of adolescence. Through their words, one discovers an opening to the world they inhabit. It is a world of silencing, shame, marginalization, self-discovery, celebration, and hope. This juxtaposition of positive and negative exemplifies their entire existence. Their words chart a course through which educators can create more supportive and caring environments that nurture academic success for all students